Protein Tyrosine Kinases From Inhibitors to Useful Drugs - Fabbro, Doriano; McCormick, Frank; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
Protein kinases function as components of signal transduction pathways, playing a central role in the control of cell growth, metabolism, differentiation, and apoptosis. The development of selective protein tyrosine kinase (PTK) inhibitors that can block or modulate diseases, such as cancer, with abnormalities in these signaling pathways is considered a promising approach for drug development. Currently, more than 20 different PTKs are being considered as potential therapeutic targets in oncology. In Protein Tyrosine Kinases: From Inhibitors to Useful Drugs, leading researchers from the Novartis group that pioneered Gleevec/Glivec™ and from around the world comprehensively survey the state-of-the-art in the drug discovery processes (bio- and chemoinformatics, structural biology, profiling, generation of resistance, etc.) aimed at generating PTK inhibitors for the treatment of various diseases, including cancer. Highlights include a discussion of the rationale and the progress made toward generating "selective" low molecular-weight kinase inhibitors; an analysis of the normal function, role in disease, and application of platelet-derived growth factor antagonists; and a summary of the factors involved in successful structure-based drug design. Additional chapters address the advantages and disadvantages of in vivo preclinical models for testing PTK inhibitors with antitumor activity and the utility of different methods in the drug discovery and development process for determining "on-target" vs "off-target" effects of kinase inhibitors. Authoritative and state-of-the-art, Protein Tyrosine Kinases: From Inhibitors to Useful Drugs details the key stages in the design of PTK inhibitors and their development into useful drugs.
Protein Tyrosine Kinases as Targets for Cancer and Other Indications -- Inhibitors of Signaling Interfaces -- PI3-Kinase Inhibition -- Src as a Target for Pharmaceutical Intervention -- Activated FLT3 Receptor Tyrosine Kinase as a Therapeutic Target In Leukemia -- JAK Kinases in Leukemias, Lymphomas, and Multiple Myeloma -- Glivec® (Gleevec®, Imatinib, STI571) -- Platelet-Derived Growth Factor -- Structural Biology of Protein Tyrosine Kinases -- Testing of Signal Transduction Inhibitors in Animal Models of Cancer -- Phosphoproteomics in Drug Discovery and Development.
Keywords: Biochemistry; Biochemistry, general